Chronic Ethanol Feeding Modulates Inflammatory Mediators, Activation of Nuclear Factor-κB, and Responsiveness to Endotoxin in Murine Kupffer Cells and Circulating Leukocytes. (29th January 2014) - Maraslioglu, Miriam; Oppermann, Elsie; Blattner, Carolin; Weber, Roxane; Henrich, Dirk; Jobin, Christian; Schleucher, Elke; Marzi, Ingo; Lehnert, Mark
Abstract : Chronic ethanol abuse is known to increase susceptibility to infections after injury, in part, by modification of macrophage function. Several intracellular signalling mechanisms are involved in the initiation of inflammatory responses, including the nuclear factor- κ B (NF- κ B) pathway. In this study, we investigated the systemic and hepatic effect of chronic ethanol feeding on in vivo activation of NF- κ B in NF- κ B EGFP reporter gene mice. Specifically, the study focused on Kupffer cell proinflammatory cytokines IL-6 and TNF- α and activation of NF- κ B after chronic ethanol feeding followed by in vitro stimulation with lipopolysaccharide (LPS). We found that chronic ethanol upregulated NF- κ B activation and increased hepatic and systemic proinflammatory cytokine levels. Similarly, LPS-stimulated IL-1 β release from whole blood was significantly enhanced in ethanol-fed mice. However, LPS significantly increased IL-6 and TNF- α levels. These results demonstrate that chronic ethanol feeding can improve the responsiveness of macrophage LPS-stimulated IL-6 and TNF- α production and indicate that this effect may result from ethanol-induced alterations in intracellular signalling through NF- κ B. Furthermore, LPS and TNF- α stimulated the gene expression of different inflammatory mediators, in part, in a NF- κ B-dependent manner.